2017
DOI: 10.12973/eu-jer.6.2.175
|View full text |Cite
|
Sign up to set email alerts
|

What Instructional Leaders Need to Know About the Effects of Inclusion

Abstract: Effective school administrators and teachers are those who provide the least restrictive learning environments for all students. The main goal of this study was to analyze the effects of inclusive science education on the general education population of middle school students' scientific conceptual understandings. The study was designed as a quasi-experimental model and conducted in a middle school in a large urban school district in Midwestern US. Approximately 4% of students in the school were receiving spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A study examining the consequences of separate schooling for children with special educational needs (SEN), demonstrated that children with SEN experience little to no positive effects [8]. Additionally, children with SEN educated in mainstream schools do better academically and socially than comparable students in special non-inclusive settings [9,7]. Blackorby and colleagues [5] established that SEN students who spent more time in inclusive classrooms had fewer absences, performed closer to grade level than peers in special needs schools, and obtained higher test achievement scores.…”
Section: Introductionmentioning
confidence: 99%
“…A study examining the consequences of separate schooling for children with special educational needs (SEN), demonstrated that children with SEN experience little to no positive effects [8]. Additionally, children with SEN educated in mainstream schools do better academically and socially than comparable students in special non-inclusive settings [9,7]. Blackorby and colleagues [5] established that SEN students who spent more time in inclusive classrooms had fewer absences, performed closer to grade level than peers in special needs schools, and obtained higher test achievement scores.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that, with the legal introduction of the concept of inclusion (PCSNA, 2000), the number of students with the status of student with special needs has increased significantly over the last two decades (Smid, 2016), and that some regulation of the processes and behaviours in this area could also be included in the school moral education plan. Inclusive classrooms also have a positive effect on the conceptual understanding of inclusion of students without disabilities (Demirdag, 2017). In line with the aim of the legislative changes of 2008, it would be reasonable to expect schools to integrate and systematically include ways of solving current moral education problems in their moral education plans, thus expanding their content beyond the prescribed content areas.…”
Section: Introductionmentioning
confidence: 99%